The molecular and cellular basis of memory engrams: mechanisms of synaptic and systems consolidation - Kupke, Janina; Oliveira, Ana (Neurobiology of learning and memory, 2025)
The capacity to record and store life experiences for periods ranging from days to a lifetime is what allows an individual to adapt and survive. Memory consolidation is the process that drives the stabilization and long-term storage of memory and takes place at two levels - synaptic and systems. Recently, several studies have provided insight into the processes that drive synaptic and systems consolidation through the characterization of the molecular, functional and structural changes of memory engram cells at distinct time points of the memory consolidation process. In this review we summarize and discuss these recent findings that have allowed a significant step forward in our understanding of how episodic memory is formed and stored in engram cells of the hippocampus and the medial prefrontal cortex.